MEETING OF FIRE SYMBOLS IN NORTHERN BACTRIAN BRONZE AGE MONUMENTS - Dilafruz Karimova (Galaxy International Interdisciplinary Research Journal, 2022)
The author in the article illustrates fire symbols in Nothern Bactra in Bronze Age.